2021
DOI: 10.2147/hiv.s300859
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS Related Knowledge of University Students in Southeast Ethiopia: A Cross-Sectional Survey

Abstract: Purpose University students are often a sexually active group that is at risk of acquiring and transmitting HIV. This risk depends on their level of knowledge towards the disease. Hence, HIV/AIDS related knowledge represents the acquisition of scientific facts and information regarding the symptoms, way of transmission, adverse consequences, and prevention strategies of the disease. Therefore, this study aimed to assess level of HIV/AIDS related knowledge among regular undergraduate students of Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…Similar to the findings from Jimma University [12], Mizan-Tepi University [13], Bahir Dar University [14], and Ethiopian Civil Service College students [15], the present study also ob- served some misconceptions among the participants on different aspects of the disease. The overall knowledge of the students on the modes of transmission and prevention was good, and the knowledge was higher among CHS students (89.3%) comparing with FBE (66.2%), which is in line with a study done at Madda Walabu University, Southeast Ethiopia [16] and Iran [17]. A possible justification for higher knowledge of health science students is that they get such kind of information in some courses as part of their curriculum.…”
Section: Knowledge On Hiv/aidssupporting
confidence: 83%
“…Similar to the findings from Jimma University [12], Mizan-Tepi University [13], Bahir Dar University [14], and Ethiopian Civil Service College students [15], the present study also ob- served some misconceptions among the participants on different aspects of the disease. The overall knowledge of the students on the modes of transmission and prevention was good, and the knowledge was higher among CHS students (89.3%) comparing with FBE (66.2%), which is in line with a study done at Madda Walabu University, Southeast Ethiopia [16] and Iran [17]. A possible justification for higher knowledge of health science students is that they get such kind of information in some courses as part of their curriculum.…”
Section: Knowledge On Hiv/aidssupporting
confidence: 83%
“…A study conducted among third-and fourth-year students from two Universities in Sudan, [15] showed that only13.8% of students had comprehensive correct knowledge of HIV&AIDS and Males showed a better level of knowledge that females. A similar study that was done in Eastern Ethiopia [16] also showed a low rate in that only 24.5% of high school adolescents had comprehensive HIV&AIDS knowledge, yet two other studies done in Ethiopia as well at Dilla University [17] and Southeast Ethiopia [18] showed a slightly higher result of 53% and 51.4% respectively, in the levels of HIV knowledge. The difference in the three study outcomes done in Ethiopia can to some extent be due to methodological differences or assessment tools used.…”
Section: Resultsmentioning
confidence: 68%
“…In addition, we also discovered that only around a third of all participants were able to accurately respond to questions about the HIV virus's incubation period (window period) and transmission from pregnant woman to the fetus. Notably, Indonesia is not the only nation dealing with this problem, while the lack of public awareness regarding HIV symptoms and mother-to-child transmission routes has been noted in various Asian and African countries, particularly among non-HIV/AIDS populations [27][28][29][30][31][32]. These ndings should be considered when developing HIV/AIDS instructional materials.…”
Section: Discussionmentioning
confidence: 99%
“…Field of study, year of study (duration of study), and monthly income were three signi cant factors. In that study, it is advised that HIV/AIDS teaching at universities should involve several years of study and that risk reduction measures should prioritize behavior modi cations [57].…”
Section: Discussionmentioning
confidence: 99%